AB0458 A PHASE II RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED, PROOF OF CONCEPT STUDY OF ORAL SELETALISIB IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME (PSS). (June 2019) - Juarez, Maria; Diaz, Nieves; Johnston, Geoffrey I.; Nayar, Saba; Payne, Andrew; Helmer, Eric; Cain, Dionne; Williams, Paulette; Ng, Wan Fai; Fisher, Benjamin; Gottenberg, Jacques-Eric; Guggino, Giuliana; et al.
Abstract : Background: Seletalisib is a potent, selective oral inhibitor of phosphoinositide-3 kinase delta (PI3Kδ). Preclinical data have shown that the PI3Kδ pathway is upregulated within salivary glands of patients with PSS and contributes to disease pathogenesis. 1 Objectives: To assess the efficacy and safety of seletalisib in patients with PSS. Methods: In this Phase II, double-blind, proof of concept study (NCT02610543 ), patients with PSS having an EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) score ≥5 were randomised 1:1 to seletalisib once daily or placebo (PBO) in addition to current PSS therapy for 12 weeks. The primary endpoint was change from baseline in ESSDAI at Week 12. The study was designed to have 80% power to detect a difference of 3.8 points in change from baseline in ESSDAI between seletalisib and PBO at Week 12 and required 58 patients to complete treatment. Other endpoints included EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI), salivary gland biopsy changes, Schirmer's I test, immunoglobulin concentrations and incidence of treatment-emergent adverse events (TEAEs). Results: The study was terminated early due to slow recruitment, which led to study power decreasing to 36%. Twenty of 27 patients randomised (seletalisib n=13, PBO n=14) completed treatment. Demographic characteristics were generally similar between groups. Mean (SE) change from baseline in ESSDAI at Week 12 was seletalisib –5.4 (1.7) vs PBO –2.8 (1.5); treatment difference vs PBO (95% CI) was –2.59 (–7.30, 2.11; p=0.266). The percentages of patients achieving a ≥3 point reduction in ESSDAI were seletalisib 66.7% vs PBO 54.5%. Post-hoc Bayesian analyses of treatment difference showed an 86.5% probability of being superior to PBO and a 48.8% probability of a >3 point difference from PBO. Clinically notable improvements in some secondary endpoints were also observed in the seletalisib group (Table 1 ). Minor salivary gland biopsies had broadly similar histological features across groups at baseline. At Week 12, seletalisib treatment led to a reduction in the size and cellular organisation of mononuclear inflammatory cell foci vs PBO (Table 2 ). TEAEs were reported by 13/13 (100.0%) seletalisib and 13/14 (92.9%) PBO patients; most frequently reported: diarrhoea (5/13 [38.5%] vs 0/14 [0%]) and headache (3/13 [23.1%] vs 2/14 [14.3%]). Serious TEAEs were reported by 3/13 (23.1%) vs 1/14 (7.1%), and discontinuations due to TEAEs by 5/13 (38.5%) vs 1/14 (7.1%) seletalisib and PBO patients, respectively. Conclusion: Although this Phase II PSS study was terminated early due to slow recruitment, seletalisib demonstrated a trend to clinical improvement in patients with PSS and acceptable safety and tolerability. Histological analyses demonstrated encouraging effects of seletalisib on the organisation and extent of salivary gland lymphocytic infiltration in patients with PSS. References: [1] Nayar S, et al. Ann Rheum Dis. 2019;78:249–260 Acknowledgement: Funded by UCB Pharma Disclosure of Interests: Maria Juarez Shareholder of: UCB Pharma, Employee of: UCB Pharma, Nieves Diaz Shareholder of: UCB Pharma, Employee of: UCB Pharma, Geoffrey I. Johnston Shareholder of: UCB Pharma, Pfizer, AstraZeneca, Employee of: UCB Pharma (and AstraZeneca + Pfizer previously), Saba Nayar: None declared, Andrew Payne Employee of: UCB Pharma, Eric Helmer Employee of: Galapagos, UCB Pharma, Takeda, Johnson & Johnson, Dionne Cain Employee of: UCB Pharma, Paulette Williams Shareholder of: UCB Pharma, Employee of: UCB Pharma, Wan Fai Ng: None declared, Benjamin Fisher Consultant for: Novartis, Roche, MedImmune, Bristol-Myers Squibb, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Giuliana Guggino Grant/research support from: Laborest, Pfizer, Consultant for: Novartis, Abbvie, Speakers bureau: Sandoz, Xavier Mariette Grant/research support from: Servier, Consultant for: AstraZeneca, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Pfizer, UCB Pharma, Marika Kvarnström: None declared, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche, Jose Rosas Consultant for: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Speakers bureau: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Juan Sanchez-Burson Speakers bureau: Lilly, Janssen, Pfizer, Roberto Giacomelli Grant/research support from: Pfizer, Actelion, Speakers bureau: Actelion, Bristol-Myers Squibb, Merck Sharp & Dohme, Abbvie, Pfizer, Sobi, Roche, Francesca Barone Grant/research support from: GlaxoSmithKline, Roche, UCB Pharma, Actelion, ONO Pharmaceutical, Consultant for: GlaxoSmithKline, Roche, Actelion, ONO Pharmaceutical, Simon J. Bowman Grant/research support from: Previously UCB Pharma (to University of Birmingham) and Roche, Consultant for: 2016-7: Novartis, Mitsubishi Tanabe Pharma 2017-8: AstraZeneca, MedImmune, GFK, Xtlbio, ONO Pharmaceutical 2018-9: Novartis, AstraZeneca, UCB Pharma